DOES PRODUCT INNOVATION ENHANCE MUSTAHIQ WELFARE THROUGH THE MEDIATION OF ISLAMIC BUSINESS SUCCESS? A PARTIAL LEAST SQUARES STRUCTURAL EQUATION MODELLING APPROACH - Tamamala, Zailan Basri; Rajasa, Muhammad Attar Indra; Ratnasari, Ririn Tri (Jurnal Ekonomika dan Bisnis Islam, 2025)
The welfare of mustahiq (zakat recipients) is one of the primary objectives of implementing productive zakat in the Islamic economic system. This study focuses on the mediating role of Islamic business success in the relationship between product innovation and mustahiq welfare. Referring to the principles of maqasid al-Shari'ah, a quantitative approach was used in this study, where primary data were obtained from micro-entrepreneurs who are recipients of productive zakat in Indonesia. Analysis using Partial Least Squares-Structural Equation Modeling (PLS-SEM) shows that product innovation significantly contributes to the success of Islamic businesses, ultimately improving the welfare of mustahiq. Furthermore, Islamic entrepreneurial motivation and entrepreneurial competency are proven to be essential factors influencing business success and its impact on sustainably improving the quality of life of zakat recipients. This study highlights the importance of a holistic approach integrating spiritual, social, and economic dimensions in zakat-based empowerment programs. These findings provide strategic recommendations for zakat institutions to design more effective interventions to support the financial independence of mustahiq and achieve the goals of sustainable Islamic social finance.